Effect of thinking style and consumption purpose on food choice: A case study with yogurt using a discrete choice experiment and eye-tracking. (December 2020) - Kim, Min-A; Yoo, Hye-Jong; Ares, Gastón; Lee, Hye-Seong
Highlights: Thinking style measured by CRT affected visual attention and choice of yogurt packages. Low reflection thinkers (LRT) gave less attention to labels than High reflection thinkers. LRT gave less importance to complex image and nutritional information for their choice. The effect of thinking style decreased when the consumption purpose was health-related. Abstract: The present study investigated the effects of thinking style, health-related consumption purpose and their interaction on food choice, using yogurt packages (plain and strawberry). For each yogurt, four 2-level label variables were used in a discrete choice experiment: image (simple vs. complex), taste description (present vs. absent), probiotics claim (detailed vs. shallow) and nutritional information (healthful vs. regular). The choice experiment was completed by 148 female study participants while their eye movements were recorded using a remote eye-tracker. The expanded Cognitive Reflection Test (CRT) was used to evaluate their thinking style. The participants' self-reports on the purpose of their yogurt consumption were used to evaluate whether or not the purpose of product consumption was associated with health, per participant. Results from the choice task showed that both CRT and health-related consumption purpose influenced the effect of image and nutritional information variables. For the participants' visual attention, the CRT significantly influenced all four label variables, while health-related consumption purpose only significantly influenced the image variable. Visual attention towards image decreased when the purpose of product consumption was associated with health. In addition, the attention towards and the importance attached to nutritional information increased with increasing CRT scores, but these effects were diminished when the participants' purpose of product consumption was related to health. These results show that the influence of thinking style on food choice may be moderated by the consumers' health-related consumption purpose.